1-Substituted-5-[(3,5-dinitrobenzyl)sulfanyl]-1H-tetrazoles and their isosteric analogs: A new class of selective antitubercular agents active against drug-susceptible and multidrug-resistant mycobacteria - Karabanovich, Galina; Roh, Jaroslav; Smutný, Tomáš; Němeček, Jan; Vicherek, Petr; Stolaříková, Jiřina; Vejsová, Marcela; Dufková, Ida; Vávrová, Kateřina; Pávek, Petr; Klimešová, Věra; Hrabálek, Alexandr (European journal of medicinal chemistry, 2014)
In this work, a new class of highly potent antituberculosis agents, 1-substituted-5-[(3,5-dinitrobenzyl)sulfanyl]-1H-tetrazoles and their oxa and selanyl analogs, is described. The minimal inhibitory concentration (MIC) values reached 1 μM (0.36-0.44 μg/mL) against Mycobacterium tuberculosis CNCTC My 331/88 and 0.25-1 μM against six multidrug-resistant clinically isolated strains of M. tuberculosis. The antimycobacterial effects of these compounds were highly specific because they were ineffective against all eight bacterial strains and eight fungal strains studied. Furthermore, these compounds exhibited low in vitro toxicity in four mammalian cell lines (IC50 > 30 μM). We also examined the structure-activity relationships of the compounds, particularly the effects on antimycobacterial activity of the number and position of the nitro groups, the linker between tetrazole and benzyl moieties, and the tetrazole itself. Relatively high variability of substituent R(1) on the tetrazole in the absence of negative effects on antimycobacterial activity allows further structural optimization with respect to toxicity and the ADME properties of the 1-substituted-5-[(3,5-dinitrobenzyl)sulfanyl]-1H-tetrazoles lead compounds.
Keywords: Cell Survival; Microbial Sensitivity Tests; Nitrobenzenes; Drug Screening Assays, Antitumor; Humans; HeLa buňky; Tumor Cells, Cultured; Tuberculosis; antituberkulotika; mnohočetná bakteriální léková rezistence; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; Tetrazole; Antineoplastic Agents; Selectivity; mikrobiální testy citlivosti; lidé; proliferace buněk; Triazoles; molekulární struktura; Drug Resistance, Multiple, Bacterial; Hep G2 Cells; nitrobenzeny; nádorové buňky kultivované; Molecular Structure; Antituberculosis drug; buňky Hep G2; Antitubercular Agents; HeLa Cells; Mycobacterium tuberculosis; Cell Proliferation; Structure–activity relationships; screeningové testy protinádorových léčiv; protinádorové látky; Mycobacterium; vztah mezi dávkou a účinkem léčiva; triazoly; viabilita buněk